1998
DOI: 10.1073/pnas.95.26.15287
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of a cDNA encoding a pheromone gland-specific acyl-CoA Δ 11 -desaturase of the cabbage looper moth, Trichoplusia ni

Abstract: Desaturation of coenzyme-A esters of saturated fatty acids is a common feature of sex pheromone biosynthetic pathways in the Lepidoptera. The enzymes that catalyze this step share several biochemical properties with the ubiquitous acyl-CoA Δ 9 -desaturases of animals and fungi, suggesting a common ancestral origin. Unlike metabolic acyl-CoA Δ 9 -desaturases, pheromone desaturases have evolved unusual regio- and stereoselective activities that contribute to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 44 publications
(37 reference statements)
4
114
0
Order By: Relevance
“…5H), which produced the C11-monounsaturated hexa-and tetradecenoates, but did not make the corresponding C18 compound when expressed in yeast by using the pYEXTHS-BN vector (19). In contrast, (Z)-11-octadecenoic acid is synthesized by yeast transformed with either pYEXTHS-BN or the YEpOLEXbased plasmids containing the T. ni ⌬ 11 desaturase gene (5,19). These differences suggest subtle dissimilarities in the tridimensional structure of the enzyme active sites, which result in different capabilities for accommodating long acyl substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5H), which produced the C11-monounsaturated hexa-and tetradecenoates, but did not make the corresponding C18 compound when expressed in yeast by using the pYEXTHS-BN vector (19). In contrast, (Z)-11-octadecenoic acid is synthesized by yeast transformed with either pYEXTHS-BN or the YEpOLEXbased plasmids containing the T. ni ⌬ 11 desaturase gene (5,19). These differences suggest subtle dissimilarities in the tridimensional structure of the enzyme active sites, which result in different capabilities for accommodating long acyl substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The desaturases expressed in female sex-pheromone glands of different moth species have evolved to play a key role in the biosynthesis of sex pheromones, exhibiting an amazing diversity of substrate and regio-and stereospecifities. Unlike the metabolic ⌬ 9 acyl-CoA desaturases, pheromone gland desaturases catalyze the formation of uncommon unsaturated fatty acyl-CoA esters with variable chain lengths, different locations of unsaturations, and either the ordinary Z or the unusual E double bond geometry (3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The structures of ⌬9 and ⌬11 desaturase-encoding cDNAs from T. ni and the corn earworm moth, Helicoverpa zea, were first characterized and reported (8)(9)(10). Research on other selected species resulted in the characterization of structures of other pheromone desaturases with different regio-and stereospecificities, including Z͞E11, E11, Z10, Z9, and Z͞E14 desaturases (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Desaturase Genesmentioning
confidence: 99%
“…Research on other selected species resulted in the characterization of structures of other pheromone desaturases with different regio-and stereospecificities, including Z͞E11, E11, Z10, Z9, and Z͞E14 desaturases (8)(9)(10)(11)(12)(13)(14)(15). Cloning studies using mRNA isolated from fat bodies and pheromone glands revealed that there were at least two classes of ⌬9 desaturases in the Lepidoptera.…”
Section: Desaturase Genesmentioning
confidence: 99%
See 1 more Smart Citation